2003
DOI: 10.1291/hypres.26.445
|View full text |Cite
|
Sign up to set email alerts
|

A 17-Year Follow-Up Study of Hypertensive and Normotensive Male University Students in Japan.

Abstract: The aim of the present study was to determine the disease course of hypertensive male university students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
2
29
1
Order By: Relevance
“…However, in this case, atherosclerosis may have been present in the vertebral artery, since the patient had out-of-office hypertension (home BP) (6), mild hyperlipidemia, and a smoking habit (7). Smoking itself is independently associated with silent cerebral infarct (8) and atherosclerotic changes (9) in Japanese. In middle-aged men, the total cholesterol level is associated with carotid atherosclerosis (10).…”
Section: Relation To Atherosclerosismentioning
confidence: 88%
“…However, in this case, atherosclerosis may have been present in the vertebral artery, since the patient had out-of-office hypertension (home BP) (6), mild hyperlipidemia, and a smoking habit (7). Smoking itself is independently associated with silent cerebral infarct (8) and atherosclerotic changes (9) in Japanese. In middle-aged men, the total cholesterol level is associated with carotid atherosclerosis (10).…”
Section: Relation To Atherosclerosismentioning
confidence: 88%
“…In terms of the proportions of hypertension (C140 mmHg for SBP and/or C90 mmHg for DBP) in Japanese young adults, Kawasaki et al [32] reported that approximately 7-20% (average, 14%) of the students at the annual regular health check at a certain university were hypertensive. Ejima et al [33] reported among university students aged less than 30 years, 13% of males and 3% of females were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study we found 17.5% of the study subjects were hypertensive. Kawasaki et al, 2003 reported that approximately 14% of the students at the annual regular health check at a certain university were hypertensive. 26 Overweight and obesity are common health conditions and their prevalence is increasing globally.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki et al, 2003 reported that approximately 14% of the students at the annual regular health check at a certain university were hypertensive. 26 Overweight and obesity are common health conditions and their prevalence is increasing globally. Several epidemiological studies reported a significant association between BMI and blood glucose.…”
Section: Discussionmentioning
confidence: 99%